Prediction of ground motion due to the influence of Nonlinear Soil Conditions using probabilistic approach - Nurhidayatullah, Eka Faisal; Dwi Kurniati (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2024)
Ground acceleration data plays an important role in obtaining accurate dynamic analysis results. This data is difficult to find in Indonesia. There is a need for a comprehensive study related to ground motion prediction by considering the condition of the soil that is able to change the acceleration which can significantly affect the building damage. The latest earthquake events and soil tests data need to be collected. Probabilistic analysis was performed to obtain the target spectra. The deaggregation analysis are used as a reference for collecting earthquake recording data. The spectral matching process is carried out according to the target spectra. Earthquake records with small errors to the target spectra are selected. Only ground motion that has the smallest deviations of acceleration, velocity, displacement, directivity and arias intensity to the original earthquake recording is used in non-linear site response analysis. Surface ground motion is obtained from the analysis of wave propagation from the bedrock to surface by considering the influence of onlinear parameters of the soil. The spectral response analysis at bedrock shows the acceleration value at 0.2 seconds period is 1.326g and 1 second period is 0.447g. Each year, the hazard is dominated with earthquakes magnitude from 6.97 to 7.23 Mw which occur in the range of 89 to 111 km with 22.20% percentage. Darfield, New Zealand ground motion from spectral matching results is the best ground motion recording that is most suitable when used at research area. Surface ground motion tends to amplify about 1.2 times.